Conservation and pastoral value of former arable lands in the agro-pastoral system of the Alta Murgia National Park (Southern Italy) - Fracchiolla, Mariano; Terzi, Massimo; D'Amico, Francesco Saverio; Tedone, Luigi; Cazzato, Eugenio (Italian Journal of Agronomy, 2017)
Grasslands are an important element of European landscapes and environment. In the last decades, several causes have contributed to their decline, among which the intensification of agriculture activities. The National Park of Alta Murgia represents a typical agro-pastoral karst system where the conversion to arable lands caused a drastic decline of semi-natural rocky grasslands of high naturalistic value that traditionally were used for sheep grazing. This change of land use created much concern about the lack of biodiversity and soil degradation. Thus, the Park Authority promotes reconversions of arable lands into grasslands to safeguard biodiversity, increase pastoralism and enhance the multi-functionality of farms. This study evaluates the conservation and pastoral value of plant communities in former arable lands derived from grasslands conversion (by crushing the rocky substrate) and subsequently abandoned. We selected seven sites of these abandoned arable lands, no longer ploughed or sown for three to five or twelve to fifteen years. In order to have a comparison with situations of low anthropic pressures, other five sites were selected in nearby natural rocky grasslands, without evidence of soil disturbance. Further two sites were selected in lands manually cleared from stones and taken out of crop production for more than fifty years. Vegetation samples were carried out according to the standard phytosociological method. Shannon and Richness indexes, ecological and phytogeographical quality and pastoral value were calculated. The ecological quality was calculated through the ratio between cover of diagnostic taxa of the higher syntaxonomic units characterising the undisturbed pastures and total cover. The phytogeographical value was evaluated considering the cover of endemic, sub-endemic and rare taxa out of the total cover value of each plant sample. For the calculation of pastoral value we considered the palatability of taxa on a scale ranging from 0 to 5 according to data found in scientific literature. From a conservation perspective, sites originated from the conversion of rocky pastures by crushing of the rocky surface showed marked differences from undisturbed grasslands, even after 15 years from abandonment. Lands manually cleared and abandoned for more than fifty years did not show appreciable differences from semi-natural grasslands, conserving many taxa of high conservation value. On the other hand, fields originated from grasslands conversion showed higher pastoral value. This paper emphasises the need for safeguarding the rocky substrates and their remnant typical grassland communities, even in the so-called quote. Results are useful for the sustainable management of the agro-pastoral system of Alta Murgia, taking into account the ecological and economic role of those lands whose rocky substrate had been crushed.